IMPACT OF THE DIVERSIFICATION STRATEGY ON THE COMPETITIVENESS OF THE AGRICULTURAL PRODUCTS MARKET (Marketing Journal, 2025)
The article analyzes the impact of diversification strategy on competitiveness in the agricultural products market. The study highlights the processes of building competitive advantages in manufacturing enterprises through product range expansion, entry in to new market segments, and the implementation of innovative marketing tools. The effectiveness of the diversification strategy is evaluated based on Porterʼs theory of competition and the Ansoff Matrix.
Keywords: diversification strategy; competitiveness; agricultural market; marketing; digital economy; innovation; Porterʼs theory; Ansoff Matrix